Cloning and functional analysis of succinate dehydrogenase gene PsSDHA in Phytophthora sojae. (July 2017) - Pan, Yuemin; Ye, Tao; Gao, Zhimou
Abstract: Succinate dehydrogenase (SDH) is one of the key enzymes of the tricarboxylic acid cycle (TCA cycle) and a proven target of fungicides for true fungi. To explore the roles of the SDHA gene in Phytophthora sojae, we first cloned PsSDHA to construct the PsSDHA silenced expression vector pHAM34- PsSDHA, and then utilized PEG to mediate the P. sojae protoplast transformation experiment. Through transformation screening, we obtained the silenced mutants A1 and A3, which have significant suppressive effect. Further study showed that the hyphae of the silenced mutant strains were shorter and more bifurcated; the growth of the silenced mutants was clearly inhibited in 10% V8 agar medium containing sodium chloride (NaCl), hydrogen peroxide (H2 O2 ) or Congo Red, respectively. The pathogenicity of the silenced mutants was significantly reduced compared with the wild-type strain and the mock. The results could help us better to understand the position and function of SDH in P. sojae and provide a proven target of fungicides for the oomycete. Highlights: There are few reports of SDH research on fungus, especially on oomycetes. We analyse the function of succinate dehydrogenase gene PsSDHA by gene silence. Study of the P. sojae pathogenicity from the perspective of TAC.